Application of ICT in Development of Agriculture Water Management Portal - NAYAK, ASHOK K; NANDA, P; SRIVASTAVA, R C; DAS, M; GHOSH, S; KUMAR, A; AMBAST, S K; PATIL, R G; KHODKE, U M; YADAV, B S (Journal of the Indian Society of Coastal Agricultural Research, 2017)
Being a Short Communication, the abstract is not available.